Adjudin - A Male Contraceptive with Other Biological Activities - Cheng, Yan-Ho; Xia, Weiliang; W.P. Wong, Elissa; R. Xie, Qian; Shao, Jiaxiang; Liu, Tengyuan; Quan, Yizhou; Zhang, Tingting; Yang, Xiao; Geng, Keyi; Silvestrini, Bruno; Cheng, Chuen-Yan (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2015)
Background: Adjudin has been explored as a male contraceptive for the last 15 years since its initial synthesis in the late 1990s. More than 50 papers have been published and listed in PubMed in which its mechanism that induces exfoliation of germ cells from the seminiferous epithelium, such as its effects on actin microfilaments at the apical ES (ectoplasmic specialization, a testis-specific actin-rich anchoring junction) has been delineated. Objective: Recent studies have demonstrated that, besides its activity to induce germ cell exfoliation from the seminiferous epithelium to cause reversible infertility in male rodents, adjudin possesses other biological activities, which include anti-cancer, anti-inflammation in the brain, and anti-ototoxicity induced by gentamicin in rodents. Results of these findings likely spark the interest of investigators to explore other medical use of this and other indazole-based compounds, possibly mediated by the signaling pathway(s) in the mitochondria of mammalian cells following treatment with adjudin. In this review, we carefully evaluate these recent findings. Methods: Papers published and listed at www.pubmed.org and patents pertinent to adjudin and its related compounds were searched. Findings were reviewed and critically evaluated, and summarized herein. Results: Adjudin is a novel compound that possesses anti-spermatogenetic activity. Furthermore, it possesses anti-cancer, anti-inflammation, anti-neurodegeneration, and anti-ototoxicity activities based on studies using different in vitro and in vivo models. Conclusion: Studies on adjudin should be expanded to better understand its biological activities so that it can become a useful drug for treatment of other ailments besides serving as a male contraceptive.
Keywords: testis